Learning Strategies in Religious Education to Foster Spiritual Values Among Generation Z - Mariana Amelda; Lers Jonson; Kuiat Kafaur; Narandina Sharema; Shalem Ahbadi (Pondok pesantren As-salafiyah As-Safi'iyyah, 2024)
This study aims to explore learning strategies in religious education to foster spiritual values among Generation Z, a cohort characterized by their deep connection to digital technology. The research method employed is library research with a descriptive-analytical approach, integrating data from various recent scholarly literatures. The results indicate that technology-based learning strategies, experiential learning, gamification, and value-based education are effective in enhancing spiritual awareness, empathy, and ethical behavior in students. Teachers play a critical role as spiritual role models, while relevant, real-life learning can overcome Generation Z's low interest in religious values. However, implementing these strategies requires technological support, teacher training, and the integration of religious values with contemporary issues. The study recommends enhancing teacher competencies, developing spiritually-based curricula, and fostering collaboration between educational institutions and communities to strengthen the application of religious values in students' lives.